"Nursing Tree Time": An inter-professional team approach to supporting student nurse learning at a regional university campus. (September 2019) - Christensen, Martin; Medew, Karin; Craft, Judy
Abstract: Providing academic and pastoral support to nursing students is important not only for ensuring success and achievement in their studies, but also to provide an inclusive environment where students have a sense of purpose and a sense of belonging. Such support is used extensively in other countries such as the United Kingdom, it is often not provided in some cases like Australia because of student cohort sizes and academic resistance to the pastoral role. The aim of this exploratory study was to evaluate the effectiveness of an inter-professional team approach to support nursing student learning. Nursing Tree Time was an academic pastoral support programme that encompassed a nursing academic, an academic skills advisor and a student welfare counsellor. For 2 h per day over two thirteen-week semesters, a nursing academic was available in the campus library to provide support and advice for any undergraduate nursing student present. Additional support was provided from an academic skills advisor and a student counsellor. A fifteen item Likert scale (1 = strongly disagree; 5 = strongly agree) with six open-ended questions was developed and administered to a convenience sample of 38 nursing students who accessed Nursing Tree Time. The results demonstrate that 80% of students were highly in favour of this type of support, 60% of students made these sessions a priority and 73% of students felt these sessions influenced them continuing with their studies. Importantly, over 94% of students agreed that the collaborative approach and access and availability this type of input improved confidence and success. A Cronbach's Alpha of 0.81 demonstrated good internal consistency. It is evident from these results that students felt there was an overwhelming need for continued academic pastoral support; however, this can prove challenging given the competing demands experienced by most nursing academics – research, teaching and governance responsibilities. Highlights: Nursing Tree Time is an effective inter-professional team approach to supporting student learning; Integral to this approach is having a nursing academic present to support student learning together with an academic skills advisor and a student counsellor. Students report feeling their confidence boosted as result of Nursing Tree Time. This approach incorporated a nursing academic, a skills advisor and a student counsellor to support learning.